Evaluación de la fertilización de tres bioproductos en el crecimiento de plántulas de café (Coffea arabica L.) en condiciones controladas en La Quinta Experimental La Argelia - Jiménez Alverca, Alex Fabián (2022)
Coffee cultivation is an article of great economic, social and cultural importance in Ecuador and Loja, however, its production is affected by, due to a low availability of nutrients in the initial stage of vegetative growth in the nursery, hence the importance of using bioproducts in order to propagate healthy and vigorous plants and thus increase their survival in the coffee plantations. This experimental research work, was carried out in the greenhouse of the Quinta Experimental “La Argelia” of the “National University of Loja”; the main was to determine the effect of the fertilization of three bioproducts TrichoTic® (T3), Raizoot® (T4), dry biomass of Azolla spp (T2) and a Control without bioproduct (SB), (T1); which were considered the treatments to evaluate the growth of coffee seedlings (Coffea arabica L.) under controlled conditions. For the definition of results, a completely randomized experimental design (CRD) was used and the variables of height, stem diameter, number of leaves per seedling were evaluated every 20 days for 120 days and the area of leaves, leaf and root dry biomass of the seedlings was evaluated only once after 120 days. According to the results of the commercial bioproducts, a better response was observed in all growth variables; thus in the Raizoot® (T4) treatment, especially in height 12.00 cm, followed by the TrichoTic® bioproduct (T3) with 11.64 cm, as opposed to the SB (T1) which obtained 11.40 cm, in all the variables evaluated. However, the Azolla treatment was negatively influenced by the acidification of the substrate. The best results in growth and development of coffee seedlings were recorded in the Raizoot® treatment (T4) in the behavior of the growth variables evaluated (Anexo 17). Keywords: Biofertilizers, beneficial microorganisms, coffee, sustainable development, agriculture.